What drives employment-unemployment transitions? Evidence from Italian task-based data - Nicola Cassandro; Marco Centra; Piero Esposito; Dario Guarascio (Global Labor Organization (GLO), 2020)
Relying on a unique longitudinal integrated database supplying micro-level information on labor market transitions (concerning the 2011-2017 period) and occupation task characteristics (e.g. routine-task intensity), this paper provides fresh evidence of the determinants of unemployment risk in Italy. We find that workers employed in routine-intensive occupations (measured with the RTI proposed by Acemoglu and Autor, 2011) do not display – on average - higher unemployment risks than the rest of the workforce. However, on distinguishing between cognitive and manual tasks, it turns out that workers employed in occupations entailing a large proportion of routine cognitive tasks (such as workers employed in service occupations as cashiers or call-center operators) are in fact exposed to a relatively higher risk of becoming unemployed. By contrast, a rather lower risk seems to be faced by workers employed in occupations entailing a large proportion of routine-manual tasks. Finally, the distribution of unemployment risk and its relation with routine-task intensity varies significantly across sectors – with higher risk in manufacturing and construction - confirming the importance of industry-level economic, technological and institutional heterogeneities.
Keywords: J24; J31; R23; 330; unemployment; routine-task; worker-level data